Anaerobic co-digestion of sugar industry press mud and raw wastewater effect of mixture composition and amount of inoculum on methane production and waste treatment performance - Sunga, Jon Errol L.; Rollon, Analiza P. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Two of the wastes generated by the sugar industry are press mud (PM) and raw wastewater (RW). The disposal of the former into the fields and the biogas generated from the anaerobic treatment of the latter left uncollected pose negative environmental effects. Anaerobic co-digestion is a treatment process wherein two or more substrates are simultaneously digested. The use of PM and RW as co-substrates for co-digestion with biogas collection system can reduce or prevent both the disposal of untreated PM and the emission of greenhouse gases into the atmosphere. Thus, in this study, the potential of PM and RW as co-substrates for anaerobic co-digestion was investigated. The effects of varying PM:RW mixtures (Pure RW, PM:RW (0:100,30:70, 50:50, 70:30, 100:0) on their characteristics, methane production and yield, and COD and solids removal were investigated using simple batch reactors. The results showed that pH and COD levels, solids content, and methane production, except for methane yield, increased with increased amount of PM. The highest cumulative methane production was obtained from PM:RW100:0) (5,565 mL CH4) while the highest methane yield was obtained from pure RW (121.58 mL CH4/g VS or 0.169 mL CH4/CH4 equivalent of initial TCOD). Among the co-digesting mixtures, PM:RW (30:70) gave the highest potential methane production (PMP). Calculations show that even if the actual industry ratio deviates from co-digesting ratios, co-digestion plus separate treatment of excess co-substrate will yield higher PMP compared to that of separate digestion. The pH level stabilized faster and methane increased by 15-20% when greater amount of inoculum is added.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Factory and trade waste -- Purification; Sewage -- Purification -- Anaerobic treatment